Chemical Composition and Antioxidant Activity of the Essential Oil of Tabernaemontana dichotoma - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2024)
Chemical Composition and Antioxidant Activity of the Essential Oil of Tabernaemontana dichotoma by Wan Mohd Nuzul Hakimi Wan Salleh